Alterations of functional connectivity in auditory and sensorimotor neural networks: A case report in a patient with cortical deafness after bilateral putaminal hemorrhagic stroke. Issue 3 (22nd January 2021) - Gwak, Dae-Won; Park, Eunhee; Park, Jin-Su; Kim, Eunji; Kang, Min-Gu; Kim, Ae-Ryoung; Lee, Jae-Eun; Jung, Seung-Hwan; Jeong, Jae-Gyeong; Lee, Kyu-Yup; Chang, Yongmin; Jung, Tae-Du
Abstract: Rationale: Cortical deafness is a rare auditory dysfunction caused by damage to brain auditory networks. The aim was to report alterations of functional connectivity in intrinsic auditory, motor, and sensory networks in a cortical deafness patient. Patient concerns: A 41-year-old woman suffered a right putaminal hemorrhage. Eight years earlier, she had suffered a left putaminal hemorrhage and had minimal sequelae. She had quadriparesis, imbalance, hypoesthesia, and complete hearing loss. Diagnoses: She was diagnosed with cortical deafness. After 6 months, resting-state functional magnetic resonance imaging (rs-fMRI) and diffuse tensor imaging (DTI) were performed. DTI revealed that the acoustic radiation was disrupted while the corticospinal tract and somatosensory track were intact using deterministic tracking methods. Furthermore, the patient showed decreased functional connectivity between auditory and sensorimotor networks. Interventions: The patient underwent in-patient stroke rehabilitation therapy for 2 months. Outcomes: Gait function and ability for activities of daily living were improved. However, complete hearing impairment persisted in 6 months after bilateral putaminal hemorrhagic stroke. Lessons: Our case report seems to suggest that functional alterations of spontaneous neuronal activity in auditory and sensorimotor networks are related to motor and sensory impairments in a patient with cortical deafness. Abstract : Supplemental Digital Content is available in the text